2020
DOI: 10.3390/su12083228
|View full text |Cite
|
Sign up to set email alerts
|

Pathways towards Sustainability in Organizations: Empirical Evidence on the Role of Green Human Resource Management Practices and Green Intellectual Capital

Abstract: According to the resource-based view (RBV), an organization can be viewed as a collection of human, physical and organizational resources. These resources are valuable and inimitable, and are the main source of sustainable competitive advantage and sustained higher performance. Green human resource management (GHRM) practices help organizations to obtaina competitive advantage and align business strategies with the environment. In the same way, increases in environmental awareness and strict implementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
3
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(203 citation statements)
references
References 80 publications
5
122
3
7
Order By: Relevance
“…Research conducted in the underdeveloped country investigates the impact of GHRM practices on the organization’s growth and shows a positive relationship between the implementation of GHRM practices and the organization’s prosperity. This past research has been conducted in the manufacturing industries; it supports the idea that the more is the GHRM practices introduced in different sectors, the more positive impact they will bring to the economy [ 84 ]. This conclusion is similar to the current research; the greater the implementation of GHRM practice—i.e., green hiring in the organization—the more the greening activities will be done, consequently achieving greater economic, social, and environmental sustainability.…”
Section: Discussionmentioning
confidence: 69%
“…Research conducted in the underdeveloped country investigates the impact of GHRM practices on the organization’s growth and shows a positive relationship between the implementation of GHRM practices and the organization’s prosperity. This past research has been conducted in the manufacturing industries; it supports the idea that the more is the GHRM practices introduced in different sectors, the more positive impact they will bring to the economy [ 84 ]. This conclusion is similar to the current research; the greater the implementation of GHRM practice—i.e., green hiring in the organization—the more the greening activities will be done, consequently achieving greater economic, social, and environmental sustainability.…”
Section: Discussionmentioning
confidence: 69%
“…The function was pursued in 34.8% of the studied entities. The popularity of green motivation was also confirmed by the studies conducted in Denmark (Forman and Joergensen, 2001) and in Pakistan (Malik et al, 2020), which showed that green motivation programs increased employee participation in pro-environmental initiatives. The lowest level of implementation was reported in the area of green recruitment.…”
Section: Figure 1 the Level Of Ghrm Implementation In The Selected Hmentioning
confidence: 80%
“…One exception is recruitment for the post of the environmental management system specialist. One should note that research carried out by different authors showed significant impact of green employee acquisition on corporate environmental effectiveness and sustainable development (Masri and Jaaron, 2017;Yong et al, 2019;Malik et al, 2020). Considering the fact the average rate of the level of implementation of GHRM in the studied entities, set as an arithmetic mean of the assessment of levels in individual areas, was 2, it is reasonable to inquire about the reason of such little interest in environmental practices in HR policy of the studied organizations.…”
Section: Figure 1 the Level Of Ghrm Implementation In The Selected Hmentioning
confidence: 94%
“…Various studies have revealed that the different elements of GHRM, such as green awareness (GAW), green skills (GS), green behaviors (GB), green attitude (GAT), green knowledge (GK) and green abilities (GAB), are essential in promoting the need for environmentalism [34]. Studies by Osborne et al [35] and Malik et al [36] confirmed that green training enhances the GAW, GS, GB, GAT, GK and GAB of employees towards improving their performances in an organization. Additionally, the resource-based theory explained that the resources of an organization that are recognized as specialized and non-replicable, are a source of numerous opportunities for heterogeneity that helps in enhancing the competitiveness of an organization [36][37][38].…”
Section: The Mediating Role Of Green Competencies Between Green Training and Green Environmental Performancementioning
confidence: 99%